Translation Analysis in Sentence Patterns Found in the Creatures Behind Houses - Juliarta, I Made (e-Journal of Linguistics, 2025)
This study aims to: (i) analyze the tree diagram structure of sentence patterns found in the story “creatures behind Houses”, (ii) analyze the types of translation shifts in sentence patterns in the translation process from source language into target language found in the data source. The story entitled “Creatures Behind Houses” is a story from Jakarta by Pramoedya Ananta Toer which was written in English and Indonesian version. This research focuses on The Syntax Analysis and Its Translation Found on Sentence Patterns in the story from Jakarta entitled “Creatures Behind Houses”. This study focuses on analyzing the tree diagram structure and the types of translation shifts found in the story entitled “Creatures Behind Houses”. The analysis uses the theory of sentence patterns proposed by Quirk and Greenbaum and the theory of translations shift proposed by Catford. The process of collecting data was started by reading the story to understand the story entitled “Creatures Behind Houses” and observe the data of sentence patterns that can be taken from the story entitled “Creatures Behind Houses”. In the method of collecting data, the data source was read to find out complex sentences and simple sentence found in the story entitled “Creatures Behind Houses”. The finding of the research is that there are seven sentence patterns that are translated by applying unit shift. The data were analyzed based on syntax, types of sentences, sentence pattern, tree diagram, and relevant previous studies. Syntax is one of the branches that focus on the sentence structure.